The Audit Expectation GAP in Indonesian Public Sector - Rambak Pongsapan (JURNAL INTEGRASI, 2012)
The purposes of this study are to tests the existence of the audit expectation gap between financial statement users and the auditors in Financial Auditing Board (BPK) as well as to identify the underlying components. The study is also to examine the difference in perception on the performance of the auditors in Financial Auditing Board (BPK) between financial statement users with basic accounting education and those without that of accounting. There are two hypotheses, as the writer wants them to test. First, there is an audit expectation gap between the financial statement users and the auditors in Financial Auditing Board (BPK), and second, there is the difference in perception on the performance of the auditors in the Financial Auditing Board (BPK) (deficient performance gap) between the financial statement users with basic accounting education and those without that of accounting. The collected data of the study gained through a survey method. They are primary data obtained from respondents as users of the financial statement of local government such as civil servants in local government, members of the House of Representatives at local levels, academics, credit analysts, and the auditors of Financial Auditing Board (BPK) in Yogyakarta. The hypotheses examined by using the Chi Square, Mann-Whitney U test and the T-Test Independent Sample. Result of the hypotheses examination indicates that the financial statement users had understanding more than the auditors did and difference in perception was significant. The financial statement users understand that the auditors have duties ideally more than their actual ones. The examination of the second hypothesis shows that there was a significant difference in perception on the performance of the auditors of Financial Auditing Board (BPK). The perception of financial statement users without that of accounting on the performance of the auditors in the Financial Auditing Board (BPK) tended to be “good”, while those with that of accounting tended to be “poor”. This research concluded as follows: first, there was audit expectation gap between the financial statement users and the auditors of Financial Auditing Board (BPK); second, there was the difference in perception on the performance of the auditors of Financial Auditing Board (BPK) between the financial statement users with that of accounting and those without that of accounting